Opera As Art: Philosophical Sketches - Thom, Paul (Lexington Books, 2022)
In Opera as Art: Philosophical Sketches, Paul Thom argues for opera as an art, standing alongside other artforms that employ visual and sonic media to embody the great themes of human life. Thom contends that in great operatic art, the narrative and expressive content collaborate with the work's aesthetic qualities towards achieving this aim. This argument can be extended to modern operatic productions. At their best, these stagings are works of art in themselves, whether they give faithful renditions of the operas they stage and whether their aims go beyond interpretation to commentary and critique. This book is a philosophical introduction to the key practices that comprise the world of opera: the making of the work; its interpretation by directors, critics, and spectators; and the making of an operatic production. Opera has always existed in a context of philosophical ideas, and this book is written for opera-lovers who would like to learn something about that philosophical context.